PENINGKATAN KOMPETENSI POKDARWIS MELALUI PELATIHAN WISATA (STUDI KASUS: SELO AJI CAMP DAN WATERPARK) - Rasidi, Ahmad Haris; Pratama, Andhika Surya; Mukarromah, Dilayatul; Fahrani, Dinda Inggar; Nugraheni, Dita Fauziah; Maulidyanu, Firdaus Putra; Handayani, Nurika; Sitio, Raffly Pandapotan; Bagaskara, Septian Tri Cahyo; Pratama, Yoga Surya; Anggara, Yudistira Dwi; Darusalam, Zulfan Riski; Prastowo, Sigit (Program Studi Agronomi Fakultas Pertanian Universitas Jember, 2024)
Indonesia, with its rich cultural diversity, has a significant tourism sector that needs to be managed optimally to attract both local and international tourists. Village-based tourism development, such as Selo Aji Camp dan Waterpark in Kaligondo Village, Banyuwangi, East Java, is increasingly popular due to its focus on cultural and environmental interaction. A community service program by KKN UMD 313 from the University of Jember aimed to enhance the digital marketing skills of the local tourism awareness group (Pokdarwis) to improve the promotion and management of Selo Aji Camp dan Waterpark. The program included collaboration with the village's BUMDes, in-depth interviews, and digital marketing strategy training. This program was held in Selo Aji Camp and Waterpark Auditorium, Selorejo hamlet. The program showed up on Tuesday, July 30, 2024. The method used in the training program was a discussion each audience or focus group discussion (FGD). The training was successful, with participants showing great interest and beginning to apply their new skills, particularly in social media management to increase the waterpark's visibility. The program also strengthened social networks among stakeholders and was expected to increase visitor numbers and improve the welfare of the Kaligondo community